Comparison of the immunogenicity and safety of quadrivalent and tetravalent influenza vaccines in children and adolescents. Issue 6 (5th February 2020) - Huang, Chenyang; Fu, Xiaofang; Zhou, Yuqing; Mi, Fenfang; Tian, Guo; Liu, Xiaoxiao; Wu, Jie; Ding, Cheng; Yan, Danying; Li, Lanjuan; Yang, Shigui
Abstract: Background: Children and adolescents are susceptible to influenza. Vaccination is the most important strategy for preventing influenza, yet there are few studies on the immunogenicity and safety of quadrivalent inactivated influenza vaccine (QIV) containing two A strains (H1N1 and H3N2) and two B lineages (Victoria and Yamagata). Therefore, to further clarify the immunogenicity and safety of QIV in children and adolescents, a meta-analysis was performed to provide a reference for the development of influenza prevention strategies. Methods: PubMed, EMBASE and Cochrane Library were searched for articles published as of February 12, 2019. Random clinical trials comparing the immunogenicity and safety of QIV and TIV among children and adolescents were selected. The main outcomes were comparisons of immunogenicity (seroprotection rate [SPR] and seroconversion rate [SCR] and adverse events using risk ratios (RRs). The meta-analysis was performed using random-effects models. Results: Among the 6 months up to 3 years group, QIV showed a higher SPR for B lineages than for TIV-B/Yamagata, with pooled RRs of 3.07 (95% CI: 2.58–3.66) and 1.06 (95% CI: 1.01–1.11), respectively. For the 3 years through 18 years, QIV had a higher SCR and SPR for the Yamagata lineage than for TIV-B/Victoria, with pooled RRs of 2.30 (95% CI: 1.83–2.88) and 1.16 (95% CI: 1.03–1.30), respectively. Compared to TIV-B/Yamagata, a higher SCR and SPR for the Victoria lineage was found for QIV, with RRs of 3.09 (95% CI: 1.99–4.78) and 1.72 (95% CI: 1.22–2.41), respectively. Regarding adverse events, only pain was more frequently reported for QIV than TIV ; the RR was 1.09 (95% CI: 1.02–1.17). Conclusions: The immunogenicity of QIV for common ingredients was similar to that of TIV, but the former exhibited significantly higher immunogenicity for the unique lineage. QIV also had the same reliable safety as TIV.